21st Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications 2010
DOI: 10.1109/pimrc.2010.5671607
|View full text |Cite
|
Sign up to set email alerts
|

Extended HSUPA coverage and enhanced battery saving opportunities with multiple TTI lengths

Abstract: 3GPP has specified that terminals can be configured to use either 2 or 10 ms transmission time interval in high speed uplink packet access systems. The purpose of this paper is to evaluate the benefit of exploiting a mixture of both of the transmissions time intervals within a cell instead of only one. The study is quantified by means of studying the achievable coverage of voice over IP and possible battery saving benefits. The analysis is conducted with a system level simulator modeling network and terminal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…. Moreover, as [2] indicates with 2 ms TTI and thus with RE the power saving opportunities are much higher than with 10 ms TTI. Taking both the improvement in capacity and the minor increase in transmit antenna activity into account, the benefits offered by RE mode clearly outweigh the negative effects.…”
Section: B Quality Of Service Criteria For Voipmentioning
confidence: 94%
See 4 more Smart Citations
“…. Moreover, as [2] indicates with 2 ms TTI and thus with RE the power saving opportunities are much higher than with 10 ms TTI. Taking both the improvement in capacity and the minor increase in transmit antenna activity into account, the benefits offered by RE mode clearly outweigh the negative effects.…”
Section: B Quality Of Service Criteria For Voipmentioning
confidence: 94%
“…Previous studies regarding HSUPA (VoIP) performance have focused on various performance enhancing techniques, such as Discontinuous DPCCH transmissions (UL DTX), i.e., Dedicated Physical Control Channel (DPCCH) gating, see, e.g., [2] [3] [4] [5] and [6]. These extensive studies for VoIP have shown noticeable gains in terms of capacity, battery savings and meeting the delay requirements.…”
Section: Motivation and Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations